2005
DOI: 10.1097/00042752-200501000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hip Muscle Weakness and Overuse Injuries in Recreational Runners

Abstract: Although no cause-and-effect relationship has been established, this is the first study to show an association between hip abductor, adductor, and flexor muscle group strength imbalance and lower extremity overuse injuries in runners. Because most running injuries are multifaceted in nature, areas secondary to the site of pain, such as hip muscle groups exhibiting strength imbalances, must also be considered to gain favorable outcomes for injured runners. The addition of strengthening exercises to specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
157
2
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(169 citation statements)
references
References 38 publications
5
157
2
5
Order By: Relevance
“…After 8 weeks of rehabilitation, the mean LEFS scores of all participants improved 12 points, surpassing the 8-point minimal detectable change suggested in previous research. 36 The LEFS has been used to determine self-reported improvements in function following therapeutic intervention for patients with PFPS. In one study, 22 participants completed 1 of 2 four-week interventions for PFPS focused on either just quadriceps exercises or a combination of hip and quadriceps exercises.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…After 8 weeks of rehabilitation, the mean LEFS scores of all participants improved 12 points, surpassing the 8-point minimal detectable change suggested in previous research. 36 The LEFS has been used to determine self-reported improvements in function following therapeutic intervention for patients with PFPS. In one study, 22 participants completed 1 of 2 four-week interventions for PFPS focused on either just quadriceps exercises or a combination of hip and quadriceps exercises.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
“…Several authors have reported that females with PFPS demonstrate weaknesses of the hip external rotators and hip abductors. 11,17,26,30,31,36,37 During functional activities, especially single-leg activities, the hip muscles prevent hip adduction and internal rotation, which may result in dysfunctional lower extremity joint alignment and can lead to the development of PFPS. 20 …”
mentioning
confidence: 99%
“…No previous research has examined the effect of neck pain duration on lower trapezius strength; however, research on hip muscle strength supports the current findings that strength deficits and symptom duration are not correlated. 28 Niemuth et al 28 found no significant interaction between hip muscle strength and duration of symptoms in recreational runners.…”
Section: Right-sided Symptoms 15mentioning
confidence: 98%
“…The actions of these segments differ: the anterior GM fiber is involved in hip abduction and internal rotation and assists flexion; the middle GM fiber is involved only in abduction of the hip; and the posterior fiber is involved in hip abduction and external rotation, and assists extension 6,7) . Weakness or injury of the GM is associated with many lower limb pathologies, including patellofemoral pain syndrome, iliotibial band friction syndrome, anterior cruciate ligament injury and lower-back pain 1,[8][9][10] ; it is also origin of abductor lurch or gluteus medius lurch and Trendelenburg gait 11) . Compared to males, females are almost twice as likely to sustain a running injury, such as patellofemoral pain syndrome, iliotibial band syndrome or gluteus medius injury 12,13) .…”
Section: Introductionmentioning
confidence: 99%